2003
DOI: 10.1080/15287390306413
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluation of Honey as an Ingredient Added to Cigarette Tobacco

Abstract: A tiered testing strategy has been developed to evaluate the potential for new ingredients, tobacco processes, and technological developments to increase or reduce the biological activity that results from burning tobacco. In the manufacture of cigarettes, honey is used as a casing ingredient to impart both aroma and taste. The primary objective of this document is to summarize and interpret chemical and toxicological studies that have been conducted to evaluate the potential impact of honey on the biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…In 2002, Paschke et al prepared a comprehensive literature review of published scientific studies of the effects of tobacco product ingredients on cigarette smoke constituents and biological activity. Additionally, Philip Morris, USA, and other major tobacco manufacturers have published on the toxicology testing of various individual ingredients and mixtures of ingredients added to cigarettes in peer-reviewed journals (Gaworski et al, 1998(Gaworski et al, , 1999(Gaworski et al, , 2007(Gaworski et al, , 2010Carmines, 2002;Heck et al, 2002;Roemer et al, 2002; Stavanja et al, 2003Stavanja et al, , 2008Baker and Bishop, 2004;Renne et al, 2006;Lemus et al, 2007;Heck, 2010;Potts et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In 2002, Paschke et al prepared a comprehensive literature review of published scientific studies of the effects of tobacco product ingredients on cigarette smoke constituents and biological activity. Additionally, Philip Morris, USA, and other major tobacco manufacturers have published on the toxicology testing of various individual ingredients and mixtures of ingredients added to cigarettes in peer-reviewed journals (Gaworski et al, 1998(Gaworski et al, , 1999(Gaworski et al, , 2007(Gaworski et al, , 2010Carmines, 2002;Heck et al, 2002;Roemer et al, 2002; Stavanja et al, 2003Stavanja et al, , 2008Baker and Bishop, 2004;Renne et al, 2006;Lemus et al, 2007;Heck, 2010;Potts et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…HY was tested (Stavanja et al, 2003) in a detailed analysis with multiple toxicological endpoints (smoke chemistry determinations, Salmonella mutagenicity testing, sister chromatid exchange, mouse skin painting study, 90-day rodent inhalation study); the study used an inclusion level of 5% (wet weight). Based upon their results, they concluded that addition of honey was acceptable from a toxicological perspective (Stavanja et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Aus den Studien der Tabakindustrie geht oft hervor, dass Additive in Zigaretten die Toxizität nicht erhöhen (Baker et al, 2004;Heck et al, 2002;Carmines, 2002Carmines, und 2004Gaworski et al, 1997;Gaworski et al, 1999;Rodgman, 2003;Roemer et al, 2002;Rustemeier et al, 2002;Stavanja et al, 2003;Vanscheeuwijck et al, 2002;Wayne und Conolly, 2002). Es ist jedoch nicht auszuschließen, dass nur eine einseitige Auswahl der Studienergebnisse stattÞ ndet.…”
Section: Allgemeine Bewertungunclassified